Anisotropic ion transport in nanostructured solid polymer electrolytes. Issue 60 (2nd July 2015) - Cheng, Shan; Smith, Derrick M.; Pan, Qiwei; Wang, Shijun; Li, Christopher Y.
<x xml:space="preserve">Abstract</x> We discuss recent progresses on anisotropic ion transport in solid polymer electrolytes.